The Joy of Retinal Painting: A Build-It-Yourself Device for Intrasaccadic Presentations. (October 2019) - Schweitzer, Richard; Watson, Tamara; Watson, John; Rolfs, Martin
As the eyes move, they incessantly impose motion blur on the retinal image, yet our perception of the world remains undisturbed. In fact, it is often assumed that intrasaccadic visual signals are largely eliminated from processing by a dedicated suppression mechanism. Here, we describe an easy-to-build presentation device that produces a stimulus that is highly salient and well resolvable during saccades: Using LED strips with high temporal resolution, any type of text and image stimulus can be presented in an anorthoscopic fashion—as if seen through and travelling behind a narrow slit—at very short durations. Whereas these stimuli appear as a brief flash during fixation, saccades spread them across the retina, producing spatially extended and well-resolved retinal images. In fact, retinally painted images induced by saccades across a series of anorthoscopic image presentations were correctly identified by observers in 90% of all cases. So why should we suppress intrasaccadic perception if it enables us to experience the joy of retinal painting?